Analysis of Clinical Manifestation at Admission and Comorbidity on Clinical Outcome of COVID-19 Patients in RSUDZA Banda Aceh - Isma, Heliyana; Arliny, Yunita; Yanifitri, Dewi Behtri; Budiyanti, Budiyanti; Zulfikar, Teuku (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2022)
Background: Coronavirus disease (COVID-19) is an infectious disease caused by the SARS-CoV- 2 virus and has become a pandemic until now. Clinical outcomes in patients vary depending on many factors, such as demographics, vital signs, laboratory results, and comorbidities.Methods: This study aims to analyze clinical outcomes in COVID-19 patients associated with the patient's general information (age, sex), demographic factors, admission vital signs, degree of symptoms at admission, blood laboratory results at admission, and comorbidities. This study is an analytic observational study with a cross-sectional design. All variables were examined based on medical records at the time of admission to the hospital. A multivariate analysis was conducted to determine what factors most influence clinical outcomes in treated COVID-19 patients.Results: There were 183 COVID-19 patients included in this study with moderate to critical degrees. Factors that influence the clinical outcome of COVID-19 patients are the presence of comorbidities, old age, high blood pressure and heart rate, anemia, leukocytosis, and increased blood sugar and creatinine at admission. Multivariate analysis showed that clinical symptoms of severe COVID-19 were a factor that influenced poor clinical outcomes in COVID-19 patients, with OR=5.6 (95% CI=2.223-13.90).Conclusion: Age, comorbidity, blood pressure, heart rate, hemoglobin, random blood glucose, and creatinine at admission influence the clinical outcome of admitted COVID-19 patients.